ANALISIS PENGARUH KOMPETENSI INDIVIDU TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT KECAMATAN RUPAT KABUPATEN BENGKALIS - Muhammad Ali Aqsa (Universitas Muhammadiyah Jambi, 2018)
This research was conducted in Rupat District Office located in District Rupat Bengkalis Regency. The purpose of this study is to determine the effect of individual competence on the performance of the employees of the Rupat District Office of Bengkalis Regency. In analyzing the data obtained from the research object, using quantitative analysis with Number of Respondents as many as 30 respondens, while the method used is a simple linear regression method. Based on the method used obtained regression equation is Y = 8.271 + 0.914 X. Based on t test results obtained t count of 5.467 larger than the ttable of 2.0484. Then Ha is accepted, so it can be concluded that Individual Competence Influential Significant Against Employee Performance Sub-District Office Rupat Bengkalis District. The great influence of individual competence on the performance of employees at the office district sub district bengkalis rupat is equal to 0,516 or 51.6%. While the rest influenced other variables that are not examined in this study.